Method for Increasing of Lens Gluing Technological Process Efficiency and a Reliable Evaluation of Output Controlled Parameters - R. V. Fiodоrtsev; E. A. Metelskaya; V. A. Marchik; A. V. Kuznetsov; A. E. Makarevich (Приборы и методы измерений, 2022)
The use of glued lens components in optical devices improves the image quality of telescopic and photographic lenses or inverting systems by eliminating a number of aberrations, and also reduces light losses in the optical system of the device. The traditional production process of lenses gluing involves the sequential execution of a set of technological operations and takes a significant period of time. The purpose of the research was to improve the accuracy and productivity of the technological process of lenses gluing by improving the optical system of the control and measuring device and automating the operation of lenses optical axes combining by introducing an electronic reference system and mechanisms for micro-movements of optical parts.A technique is proposed for centering of two and three-component optical blocks by an autocollimation flare which provides a matching accuracy of less than 0.5 μm. The possibility of constructive modernization of the classic ST-41 autocollimation microscope with parallel separation of the displayed output information in the visual and television channels is shown. An automated system for controlling of the process of convergence of autocollimation points in the device is proposed. Using software methods an electronic grid template is formed on the monitor screen, onto which images of autocollimation points are projected. The decentering value 2Δe is determined and a corrective control voltage is applied to three stepper motors and pushers for transverse movement of the glued optical part.Specialized software has been developed for automatically bringing the position of the autocollimating crosshair to the center of the measuring scale of the grid based on a combination of two methods of “least squares” and “successive approximation”. Compliance with a number of technological transitions and the accompanying control of geometric parameters make it possible to achieve greater accuracy in determining the eccentricity of the crosshairs of the aligned optical axes of the glued lenses.